2013
DOI: 10.1111/jvp.12065
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma gallisepticum and Escherichia coli mixed infection model in broiler chickens for studying valnemulin pharmacokinetics

Abstract: A Mycoplasma gallisepticum-Escherichia coli mixed infection model was developed in broiler chickens, which was applied to pharmacokinetics of valnemulin in the present experiment. The velogenic M. gallisepticum standard strain S6 was rejuvenated to establish the animal model, and the wild E. coli strain O78 was injected as supplementary inoculum to induce chronic respiratory disease in chickens. The disease model was evaluated based on its clinical signs, histopathological examination, bacteriological assay, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
4
19
0
Order By: Relevance
“…The significant correlation between dose and AUC 24 (R 2 ϭ 0.9899) allows us to calculate the AUC 24 for other dosages. This phenomenon was confirmed in other research, i.e., for marbofloxacin PK in pigs within doses ranging from 4 to 16 mg/kg (26); however, our estimated PK parameters were somewhat different from those published previously for chickens infected by M. gallisepticum plus Escherichia coli (17). After i.m.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The significant correlation between dose and AUC 24 (R 2 ϭ 0.9899) allows us to calculate the AUC 24 for other dosages. This phenomenon was confirmed in other research, i.e., for marbofloxacin PK in pigs within doses ranging from 4 to 16 mg/kg (26); however, our estimated PK parameters were somewhat different from those published previously for chickens infected by M. gallisepticum plus Escherichia coli (17). After i.m.…”
Section: Discussionsupporting
confidence: 81%
“…This difference may be explained by age and pathological situation. In our study, M. gallisepticum caused only respiratory system injury in 9-day-old chickens, while the injury from M. gallisepticum plus E. coli affected the whole body (lungs, liver, kidneys, heart, and others) in the adult chicken (17). These results emphasize the influence of age and physiological status on pharmacokinetics (27,28).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The data from the present multiple dosage studies of tiamulin confirmed the conclusion that the AUC 24h /MIC was the PK/PD index of tiamulin. The values of AUC 24h /MIC for mycoplasmastasis (0 log 10 ccu equivalents reduction), activity of 1 log 10 ccu equivalents reduction, and 2 log 10 ccu equivalents reduction were 124, 205, and 327 h, respectively, which were much lower than those obtained from an in vivo study of valnemulin (28,820, 38,030, and 56,256 h, respectively) (36). One possible reason for the differences was that the concentration in serum was not that real one act on M. gallisepticum as the infection site is air sac or respiratory system, and antibiotic concentrations in air sac or lung are usually different from those in serum (14).…”
Section: Discussionmentioning
confidence: 74%
“…On the one hand, MG can invade and cohabit with non-phagocytic host cells, such as Hela cells, chicken erythrocytes, and chicken embryo fibroblasts (CEF), and inner organs of chickens in a parasitic way for a long time [6,7]; on the other hand, the majority of surface antigens of MG are highly variable [5,8]. Despite great advances in promoting antibiotic and vaccine sensitivity, MG infection still occurs frequently in chickens of different ages, especially in the presence of co-infections, bringing great economic losses to poultry industry [9,10,11,12]. Therefore, clarification of the molecular mechanism of MG infection is urgently needed.…”
Section: Introductionmentioning
confidence: 99%